PROFIL PENDERITA KARSINOMA ENDOMETRIUM DI RSUD ARIFIN ACHMAD PEKANBARU PERIODE 2008 - 2013 - Anggelina Effendi; Wiwit Ade Fidiawati; Ruza P. Rustam (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Endometrium carcinoma is epitel primer malignant tumour in endometrium, generaly the differential of grandular and have potential into myometrium. There are two kind histological type of endometrium carcinoma, 1) endometrium adecarcinoma type I with histological type (endometrioid adenocarcinoma) with well differentiated caracteristic and supervitial invasion. 2) endometrium adecarcinoma type 2 with poorly differentiated or agresif histologic type (clear cell, papiler serous) invasion into myometrium. Most of endometrium carcinoma cases commonly related to cronic endometrium estrogen stimulation which is related to type I of endometrium carcinoma. the purpose of this research is to indentified patient’s profile of endometrium carcinoma in RSUD arifin ahmad pekanbaru period 2008-2013. Sample were taken by a histopatologic diagnose in patologic anatomy department of RSUD arifin ahmad pekanbaru. The amount of carcinoma patient period 2008-2013 is about 58 cases and just 43 cases have complete profile. The profile is about age, parity and histopatologic type. Based on the result of the data , it can be concluded that the most amount of endometrium carcinoma is in range of age 41-50 years old (45%), the most parity is in 0 parity (nuliparitas) (54%), and the most histopatologic type is endometrioid adenocarcinoma (90%).Key words : Endometrium Carcinoma, Endometrium carcinoma type 1, Endometrium carcinoma Type 2PENDAHULUANKarsinoma endometrium adalah tumor ganas epitel primer